Body dysmorphic disorder patients: Their affective states, personality disorder functioning styles and body image concerns. (1st September 2018) - He, Wenxin; Shen, Chanchan; Wang, Chu; Jia, Yanli; Wang, Jiawei; Wang, Wei
Abstract: Background: Body dysmorphic disorder involves relatively stable characteristics of body image concerns and personality and is comorbid with depressive and bipolar disorders. There is, however, no clear picture of the associations between the affective states and personality features in this disorder. Methods: Therefore, we invited 142 patients with body dysmorphic disorder and 226 healthy volunteers to undergo tests involving the Body Image Concern Scale, Personality Measure, Mood Disorder Questionnaire, Hypomanic Checklist-32, and the Plutchik - van Praag Depression Inventory. Results: Patients scored significantly higher on all scales than healthy volunteers. Schizotypal and avoidant personality disorder styles and hypomania and depressive levels were positively associated with some body image concern scales in the two groups. Regarding associations between personality and body dysmorphic features, depression acted as a mediator in both groups, and hypomania served as an additional mediator in patients. Conclusions: Our study identified more body image concerns and personality and affective dysfunctions; revealed the associations between body image concerns and personality and affective characteristics; and determined that depression and hypomania were mediators between body image concerns and personality features in patients with body dysmorphic disorder. Highlights: Body dysmorphic disorder patients had personality and affective dysfunctions. Affective states were associated with body image concerns and personality. Depression and hypomania were mediators between them in patients.